KONSEP PENGUATAN IMAN KEPADA HARI AKHIR DALAM AL-QUR’AN DAN IMPLIKASINYA DALAM KEHIDUPAN - sulis; Khanifah, Umi Nurul; Anggraini, Novita Nur; Waliko (STQINIS, 2024)
A person's behavior is closely related to his faith in Allah and the last day. The phenomenon of declining morals indicates the weakness of one's faith which results in damage to society and even the nation. For this reason, the right steps are needed to strengthen faith in the last day. With this research, the author tries to explain the concept of strengthening faith in the last day in the Qur'an and its implications in his life. The method used in this research is a qualitative method with a library research approach. Data analysis was performed using content analysis techniques. The primary data source in this study was the thematic Al-Qur'an of the Ministry of Religion of the Republic of Indonesia while the secondary data source was obtained in literature by seeking information and data in the form of journals, books, and social media related to research. Based on the results of the study, one of them was found at 1Al-yaum al-akhir, yaumulqiyamah, yaumul-hasyr, yaumul reckoning, yaumud-din or yaumuljaza', yaumud-tanad, yumut talaq, yaumulfasl, yaumulTagabun. As for the implications for life, it will encourage humans to be better and aware of their every action. Keywords: faith, last day, as-sa'ah